PENINGKATAN STRATEGI PROMOSI BERBASIS METODE ANALYTICAL HIERARCHY PROCESS (AHP) DALAM SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN MAHASISWA BARU: Enhancing Promotion Strategies Using the Analytical Hierarchy Process (AHP) Method in a Decision Support System for New Student Admissions - Abdul Hamid Arribathi; Esmeralda Esmeralda (Universitas Wiralodra, 2026)
There are still some universities and colleges in accepting new students where the selection process and the promotion strategy implemented are still general and not fully based on in-depth data and analysis. For this reason, the development of information technology can be used to build a decision support system (SPK) to help the selection process for new student admissions that is more objective, measurable, and systematic. One of the relevant methods in decision-making is the Analytical Hierarchy Process (AHP). This method is able to break down complex problems into simpler structures and calculate the weight of each of the criteria that are considered important. With the application of the AHP method in SPK, a university or college can determine priorities in the selection of prospective students and evaluate the effectiveness of the promotion strategy that has been carried out based on the analyzed data. Thus, it can improve the quality of new student admissions while optimizing resources in campus promotion.